2015
DOI: 10.1371/journal.pone.0132950
|View full text |Cite
|
Sign up to set email alerts
|

Divide and Conquer May Not Be the Optimal Approach to Retain the Desirable Estrogenic Attributes of the Cyclopia Nutraceutical Extract, SM6Met

Abstract: The genus Cyclopia, an indigenous South African fynbos plant used to prepare honeybush tea, contains phytoestrogenic compounds. An extract from C. subternata, SM6Met, displays three desirable estrogenic attributes for future development of a phytoestrogenic nutraceutical, namely, ERα antagonism, ERβ agonism, and also antagonism of E2-induced breast cancer cell proliferation. Activity-guided fractionation of SM6Met was used in an attempt to isolate and identify compounds conferring the desirable estrogenic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Many phenolic compounds with health promoting benefits have been identified in C. subternata ( De Beer et al, 2012 ; Kokotkiewicz et al, 2012 ). SM6Met is a well-characterized phytoestrogenic extract of C. subternata with a comparable estrogenic potency to commercially available phytoestrogenic nutraceuticals ( Mfenyana et al, 2008 ; Mortimer et al, 2015 ). Previous work from our group have shown that SM6Met antagonizes estrogen-induced BC cell proliferation in vitro ( Visser et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many phenolic compounds with health promoting benefits have been identified in C. subternata ( De Beer et al, 2012 ; Kokotkiewicz et al, 2012 ). SM6Met is a well-characterized phytoestrogenic extract of C. subternata with a comparable estrogenic potency to commercially available phytoestrogenic nutraceuticals ( Mfenyana et al, 2008 ; Mortimer et al, 2015 ). Previous work from our group have shown that SM6Met antagonizes estrogen-induced BC cell proliferation in vitro ( Visser et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study showed that the presence of lipids in extracts containing phenolic compounds, as found in ID7, helps in the solubilization of these substances in the cells, which may potentiate their activity [17] explaining the relationship of these compounds with the results found. It is not clear yet, whether the observed activity might be due to a synergistic effect of the mixture of compounds in ID7-analogues to observed activity in fighting breast cancer with SM6Met from honey bush te [18].…”
Section: Discussionmentioning
confidence: 99%
“…From the guided fractionation of SM6Met it was observed that it is unlikely that only one compound will be responsible for the estrogenic attributes, but rather that various compounds contribute to the activity of the extract either individually (additive) or inducing a synergistic effect [38]. The idea of intelligent mixtures in the investigation of activity, induced by a mixture of compounds, has become increasingly popular [18]. Thus, it is believed that the five compounds recognized in ID7 can act synergistically providing antitumor and antimetastatic activities found in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The COS-1 monkey kidney and HEK293 human embryonic kidney cell lines were obtained from the ATCC and cultured as previously described [12,15]. Only mycoplasma-negative cell lines were used in experiments.…”
Section: Methodsmentioning
confidence: 99%